2017
DOI: 10.1002/ange.201711190
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed, Regioselective Oxidation of Saturated Hydrocarbons in an Ambient Corona Discharge

Abstract: Atmospheric pressure chemical ionization (APCI) in air or in nitrogen with just traces of oxygen is shown to yield regioselective oxidation, dehydrogenation, and fragmentation of alkanes.Ozone is produced from ambient oxygen in situ and is responsible for the observed ion chemistry,w hich includes partial oxidation to ketones and C À Cc leavage to give aldehydes.T he mechanism of oxidation is explored and relationships between ionic species produced from individual alkanes are established. Unusually,dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For instance, complexes with single (14-32) and multiple (15,(33)(34)(35)(36)(37)(38)(39) transition metal centers, small metal clusters (40)(41)(42)(43)(44)(45)(46)(47)(48), and also, main group compounds (49-52) have been found to be able to split dinitrogen. The activation of N-N bonds by oriented external electric fields (53,54) followed by insertion of, for example, a nitrogen atom in the C-C bonds of alkanes has been reported as well (55,56). Another promising approach is based on the electrochemical cleavage of N 2 to produce ammonia (11,31,32,51,(57)(58)(59)(60).…”
mentioning
confidence: 99%
“…For instance, complexes with single (14-32) and multiple (15,(33)(34)(35)(36)(37)(38)(39) transition metal centers, small metal clusters (40)(41)(42)(43)(44)(45)(46)(47)(48), and also, main group compounds (49-52) have been found to be able to split dinitrogen. The activation of N-N bonds by oriented external electric fields (53,54) followed by insertion of, for example, a nitrogen atom in the C-C bonds of alkanes has been reported as well (55,56). Another promising approach is based on the electrochemical cleavage of N 2 to produce ammonia (11,31,32,51,(57)(58)(59)(60).…”
mentioning
confidence: 99%
“…Furthermore, these products formed on a mass-spectrometric timescale. These reactions have been decoupled from a mass spectrometer with the gas-phase products collected offline for determination with other techniques (Ayrton et al, 2018). In a corona discharge reactor under a reflux for 3 hr, octane was oxidized and unsaturated regioselectively to form only 3-octen-2-one as characterized by GC-MS.…”
Section: B Plasma Ionization For Faster and More Efficient Chemical Synthesesmentioning
confidence: 99%
“…Generally, GC-APCI is well known to generate molecular weight diagnostic M + • and [M+H] + ions [35,36]. However, a few studies demonstrated that in ambient corona discharge, the addition of N and O to hydrocarbons via ion/molecule reactions is possible [37]. In this work, we carried out an ionization experiment by injecting individual 100 pg/L methanolic solutions of adiponitrile, furfural, methyl palmitate, and dipropyl phthalate into the APGC-Q (Supplementary 2).…”
Section: Advances In Apgc Ionization Pathwaysmentioning
confidence: 99%
“…When ionization takes place in a nitrogen atmosphere with traces of oxygen at low corona current, nitrogen addition is strongly favored over oxygen addition. At higher currents, the opposite is true [37]. Oxygen is known to produce ozone in corona discharges [39] and is likely responsible for the oxidation processes, including dipolar insertion and protonation to [M+3O+H] + , and sequential loss of one or two molecules of water, obtaining [M+2O−H] + and [M+O-3H] + .…”
Section: Advances In Apgc Ionization Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation